PENGARUH MODEL CREATIVE PROBLEM SOLVING DENGAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA MATERI PECAHAN KELAS 4 SDN KARANGTANJUNG - Athiyah Maqbulah; Muhammad Assegaf Baalwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low mathematical problem-solving ability of fourth-grade elementary school students, especially in fraction material. Many students have difficulty in understanding descriptive questions and in applying mathematical concepts in everyday life. The purpose of this study was to determine the effect of the Creative Problem Solving (CPS) model with the Realistic Mathematics Education (RME) approach on the mathematical problem-solving ability of fourth-grade elementary school students at SDN Karangtanjung. The research method used was quantitative with a one-group pretest-posttest design. The research sample consisted of 29 fourth-grade students. The research instrument was a descriptive test sheet of 10 questions, arranged based on the problem-solving ability indicators according to Polya, including understanding the problem, planning a solution, implementing the plan, and evaluating the results. Data were analyzed using the Paired Sample t-Test. The results showed a significant increase in the posttest results compared to the pretest. This is evidenced by the Sig. (2-tailed) value of 0.000 <0.05, which indicates that the application of the CPS model with the RME approach has a significant effect on students' mathematical problem-solving abilities. Thus, the CPS learning model combined with the RME approach is effective in improving conceptual understanding and mathematical problem-solving skills in fraction material.